Canolfannau Cymraeg a Rhwydweithiau Cymdeithasol Oedolion sy'n dysgu'r Gymraeg: Ymdrechion i Wrthdroi Shifft Ieithyddol mewn Cymunedau cymharol ddi-Gymraeg - Steve Morris (Academi Hywel Teifi, 2011)
This report is based on research commissioned by the Department of Education and Skills in the Welsh Government. The main research questions addressed look at the social networks of adult learners of Welsh and whether these are enhanced by studying in a Canolfan Gymraeg. It proposes the the model of the Canolfan Gymraeg should be emulated in the more anglicised areas of Wales as a means of increasing learners' contact and integration with the Welsh language in areas where Welsh is not the main language of the community. There are numerous strategies and models proposed for taking this forward and the report includes an endorsement from Professor Colin Williams a world leader in language planning. The report was completed in 2011 and launched at the Senedd in Cardiff in July 2012.